ELBOW JOINT RADIOGRAPHY EXAMINATION TECHNIQUE WITH FRACTURE CLINICAL IN PEKANBARU MEDICAL CENTER HOSPITAL INSTALLATION - Wenda Erliyanda; Muhammad Wildan (LPPM Universitas Awal Bros, 2025)
Elbow joint radiography is a fundamental diagnostic imaging examination that utilizes X-rays toevaluate the anatomical structures of the elbow joint and identify abnormalities, particularly fracturesinvolving the distal humerus. Accurate radiographic positioning is essential to produce optimal imagequality and provide sufficient diagnostic information for appropriate clinical management. Fractures ofthe humeral condyle require precise imaging to assess the fracture line, displacement, and involvementof the articular surface, thereby assisting physicians in determining the most appropriate treatment. Thisstudy aimed to describe the radiographic examination technique of the elbow joint in a patient with aclinical diagnosis of a left humeral condyle fracture at the Radiology Department of Pekanbaru MedicalCenter Hospital.This study employed a qualitative descriptive method using a case study approach. Data were collectedthrough direct observation of the examination procedure, interviews with the referring physician,radiographers, and the patient's family, as well as documentation of the radiographic examinationprocess. The examination protocol included patient preparation, positioning, exposure factor selection,and image evaluation. Radiographic examination was performed using two standard projections,namely anteroposterior (AP) and lateral projections, with a cassette size of 35 × 43 cm and a focus-tofilmdistance(FFD)of 100cm. TheresultsshowedthattheAPprojectioncouldnotbeperformedaccordingtothestandardpositioning technique because the patient's limited cooperation and pain restricted proper arm positioning.Consequently, the AP image was slightly modified while maintaining adequate visualization of thefracture. In contrast, the lateral projection was performed according to standard radiographic proceduresand provided satisfactory visualization of the elbow joint. The study concludes that radiographicexamination of the elbow joint in patients with left humeral condyle fractures may require positioning modifications based on the patient's clinical condition while maintaining diagnostic image quality to support accurate diagnosis and treatment planning.